Upaya Guru Kelas Dalam Meningkatkan Disiplin Pada Anak Usia 4-5 Tahun Melalui Metode Pembiasaan - Purwani, Lilis; Ishma, Noor (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
This research started from the background of the lack of understanding of the class teacher regarding instilling discipline in children from an early age, namely awareness in discipline including, arriving on time, obeying class rules, tidying up toys after use, queuing and being orderly. The formulation of the problem in this paper is how the class teacher's efforts in improving the discipline of children aged 4-5 years through the method of habituation. The purpose of this study is to describe the discipline of children aged 4-5 years through the method of habituation. This writing is Classroom Action Research, which is carried out through 3 cycles with each cycle of stages being planning, implementing, observing and reflecting. This writing took place in Darunnajah Islamic Kindergarten 1. The data was collected by observation, interviews and documentation. The results of the writing show: 1) The results showed an increase in discipline with the habituation method in the first cycle which was in the category of developing according to expectations amounting to 56.4%, then in the second cycle it became 83.3% and in the third cycle it reached 93.6%. 2) Children's discipline can be improved by the habituation method by providing examples to students, providing motivation, in instilling discipline carried out continuously and consistently. Besides that, it is also accompanied by clapping and songs, reading Islamic stories, accompanied by giving rewards in the form of praise and star stickers.